Awareness Without Access: Exploring University Students’ Perceptions of SRH Education in Nepal (International Journal of Atharva, 2025)
Sexual and Reproductive Health (SRH) education is a very important aspect for the overall development of students. However, in a conservative educational context like Nepal, this topic has not yet received enough attention, due to which it has become an under-addressed topic. The aim of this study was to understand the perceptions of university-level students on SRH education. A quantitative approach was used for this. Supplementary qualitative data were used only for triangulation. A census sampling method was adopted. An online survey form was distributed to all 769 undergraduate students of the Faculty of Education. Despite several follow-ups, only 480 students responded. Thus, the response rate was 62.4%. To further enrich the findings, six students from non-health backgrounds were purposively selected. Out of them, three were male and three were female. In-depth physical interviews were conducted with them. Chi-square test was used for quantitative data analysis. Thematic analysis was adopted for data triangulation.The results showed that 87.5% of the students understood the importance of comprehensive sexuality education (CSE). Similarly, 90.6% of the students said that early intervention is needed to inform about it. However, a large gap was still seen in CSE access. Only 36.2% of students believed that their college provided adequate resources for sexuality information. Similarly, only 53.1% of students felt that a safe space was needed to discuss CSE. For female students, social stigma was a major barrier to accessing information on sexuality. Bivariate analysis showed that students who were male, older (26-35 years) and had highly educated parents, especially mothers, had more positive perceptions about SRH (sexual and reproductive health). Students have high awareness regarding SRH. However, due to social structures and cultural barriers, they do not have access to adequate knowledge. Therefore, colleges should include gender-sensitive and inclusive SRH education not only in health subjects but also in other subjects, which helps break the cycle of stigma and silence. Additionally, counseling services need to be provided to create a safe and supportive environment where all students can access reliable and competent health information.